Gender differences in antibiotic use behaviour and access to antibiotics in low- and middle-income countries: a scoping review protocol - Sarah Hotham; Simon Bailey; Rebecca Cassidy; Oluwafemi J Adewusi; Aaron Aboderin (BMJ Open)
Introduction In low- and middle-income countries (LMICs), the persistent lack of access and high inappropriate use of antibiotics, which are fuelled by gender-related factors, continue to facilitate antimicrobial resistance. This in turn reduces the capacity to treat infectious diseases. However, there is a lack of clarity on the nature and extent of the available evidence on gender influence on access to antibiotics and antibiotic use behaviour. This proposed study will systematically review the available literature to map out the scope of evidence on gender differences and, importantly, the related factors influencing antibiotic use and access to antibiotics in LMICs.Methods and analysis This scoping review will be conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines for scoping reviews. Major databases (MEDLINE, PsycINFO and CINAHL) will be searched via the EBCOhost and Web of Science platforms for peer-reviewed articles. Title and abstract screening, as well as full paper review, will be conducted by a single reviewer, with 20% of identified citations reviewed independently by two other reviewers. A predefined excel spreadsheet will be used for data extraction and analysis. Findings will be presented thematically in a narrative summary and tables.Ethics and dissemination Obtaining ethics approval is not required for this study. The findings will contribute to understanding gender health inequalities and areas for further research on strategies to incorporate gender considerations in antimicrobial stewardship efforts in LMICs. The study findings will be disseminated through presentations in seminars, scientific conferences and publications in peer-reviewed journals.